KARAKTER DAN WARNA LOKAL CERPEN-CERPEN JAWA POS TAHUN 2000 - Mashuri, NFN (Balai Bahasa Kalimantan Tengah, 2017)
This research is trying to describe short stories in Jawa Pos written by East Java writers during 2000s. The purpose of the study is to explain local wisdom and characteristic among East Java people. Using the characterization and stylistic analysis, it turns out that the fictional characters in those East Java short stories are not merely single entity. The fact is actually correspondences with the multiethnics East Javanese socio-cultural values since it strongly influenc the East Java writers. However, black humour is the dominant factor as the style besides sarcastic, satire, and irony. Those writers are not only focusing on subculturally local wisdom and kampong values, but also interested in urban problems with its magic realism, sufism themes, and religiosity. Localities as the socio-cultural background are namely Arekan, Pesisir, Mataraman, and Madura. Therefore, we can conclude that short stories in Jawa Pos during 2000s have discourse transition in terms of millennium shift context, containing local issues which side-by-side with global matters as its themes